Invariants and variants of bahareque in the Zulia state - Henneberg de León, Andrea Mara (Rev. Téc. Fac. Ing. Univ. Zulia)
Bahareque is an original constructive technique of the pre-Hispanic era that has survived to the present time in the region of Zulia. For the sake of deepening the knowledge of this technique in our region, this work undertakes the study of the constructive aspects and the materials used in several houses done of bahareque, to determine its invariants and variants. For this purpose were observed and surveyed a sample of 17 houses in different urban, sub-urban and rural areas, which can be considered “old”, because they were constructed before 1950. The results of the collected information were analized applying the comparative method and then with the deductive method were enunciate those aspects which are equal and those which arenÂ´t. It is possible to concluded that differences as far as the technique itself were not observed; the distinctions appear in relation to the used materials which in most cases come from the surroundings.